PREDIKSI LOCUS OF CONTROL INTERNAL DAN KECERDASAN EMOSI DENGAN KEMATANGAN KARIR - Siti Maesaroh; Sinta Saraswati (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2020)
Abstract: This research aims to identify the relationship between internal locus of control and emotional intelligence with career gains. This study uses a correlational design. Data were collected using an internal locus of control scale, a scale of emotional intelligence, and a career scale of 247 students selected by a random sampling quota technique. Hierarchical regression analysis results showed a positive prediction between internal locus of control and emotional intelligence with very significant career gains (R = 0.555, F = 54,374, p <0,000). The implications of the findings of this study are discussed in this article. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi hubungan antara locus of control internal dan kecerdasan emosi dengan kemtangan karir. Penelitian ini menggunakan desain korelasional. Data dikumpulkan dengan menggunakan skala locus of control internal, skala kecerdasan emosi dan skala kemtangan karir dari 247 siswa yang dipilih dengan teknik kuota random sampling. Hasil analisis regresi hierarkis menunjukan prediksi positif antara locus of control internal dan kecerdasan emosi dengan kemtangan karir yang sangat signifikan (R= 0,555, F=54,374, p<0,000). Implikasi dari temuan penelitian ini dibahas dalam artikel ini. Abstract: This research aims to identify the relationship between internal locus of control and emotional intelligence with career gains. This study uses a correlational design. Data were collected using an internal locus of control scale, a scale of emotional intelligence, and a career scale of 247 students selected by a random sampling quota technique. Hierarchical regression analysis results showed a positive prediction between internal locus of control and emotional intelligence with very significant career gains (R = 0.555, F = 54,374, p <0,000). The implications of the findings of this study are discussed in this article. Keywords: internal locus of control, emotional intelligence, career maturity Abstrak: Penelitian ini bertujuan untuk mengidentifikasi hubungan antara locus of control internal dan kecerdasan emosi dengan kemtangan karir. Penelitian ini menggunakan desain korelasional. Data dikumpulkan dengan menggunakan skala locus of control internal, skala kecerdasan emosi dan skala kemtangan karir dari 247 siswa yang dipilih dengan teknik kuota random sampling. Hasil analisis regresi hierarkis menunjukan prediksi positif antara locus of control internal dan kecerdasan emosi dengan kemtangan karir yang sangat signifikan (R= 0,555, F=54,374, p<0,000). Implikasi dari temuan penelitian ini dibahas dalam artikel ini. Kata kunci: Locus Of Control Internal, Kecerdasan Emosi, Kematangan Karir